2018
DOI: 10.1038/s41598-017-18574-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Plasmodium falciparum in Infants is associated with Low, not High, Placental Malaria Parasitemia

Abstract: Risk of malaria in infants can be influenced by prenatal factors. In this study, the potential for placental parasitemia at delivery in predicting susceptibility of infants to Plasmodium falciparum (Pf) infections was evaluated. Seventy-two newborns of mothers who were placental malaria negative (PM−) and of mothers who were PM+ with below (PM+ Lo) and above (PM + Hi) median placental parasitemia, were actively monitored during their first year of life. Median time to first PCR-detected Pf infection was shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…One study demonstrated that children born to mothers with placental malaria had a significantly higher odds of clinical malaria (OR, 4.1; 95% CI, 1.3-13.1) in the first year of life [54]. Another study found that clinical malaria episodes occurred earlier in children born to women with placental malaria than women with no placental malaria [57]. Congenital malaria, while rare, has been associated with placental malaria.…”
Section: Obstetrical Outcomesmentioning
confidence: 99%
“…One study demonstrated that children born to mothers with placental malaria had a significantly higher odds of clinical malaria (OR, 4.1; 95% CI, 1.3-13.1) in the first year of life [54]. Another study found that clinical malaria episodes occurred earlier in children born to women with placental malaria than women with no placental malaria [57]. Congenital malaria, while rare, has been associated with placental malaria.…”
Section: Obstetrical Outcomesmentioning
confidence: 99%
“…Furthermore, maternal malaria infection profoundly impacts the postnatal health and survival of the infants. Malaria-associated low birth weight is estimated to have a fatality rate of 37·5% [22], and infants born to malaria-infected women are more susceptible to malaria in early life [[23], [24], [25]]. Thus, understanding the pathogenesis of malaria in pregnancy is critical for improving maternal and child health outcomes in malarious regions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in high transmission areas have reported little or no increase in Ab avidity with age for EBA-175, MSP1, MSP2, and MSP3 [4][5][6][7][8][9]. Plasma used in this study was from infants and adults living in a rural village with perennial transmission who received an estimated 257 infectious mosquito bites/person/year [29,30]. Clearly, it would be interesting to investigate affinity maturation with age in this high transmission setting to determine if and when affinity maturation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…A collection of de-identified, archival, plasma samples from malaria endemic regions of Cameroon with high transmission were used [29,30]. Samples included: plasma from 5 selected adults with known Ab levels for the antigens; 40 adults residing in Ngali II (pregnant women, non-pregnant women, males) who had been repeatedly infected with malaria and had developed high malarial immunity, and 57 12-month-old infants living in Ngali II who had just begun developing immunity to malaria [30].…”
Section: Plasma Samplesmentioning
confidence: 99%
See 1 more Smart Citation